2023
DOI: 10.1007/s10661-023-11475-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the danger of a tailings pile belonging to an active mine through its characterization and a dispersion model

Abstract: Mining is one of the principal economic activities in Mexico, which in addition to bringing benefits to the population, causes health and environmental problems. This activity produces a lot of wastes, but the main one is tailings. In Mexico, these wastes are disposed of in the open air, and there is no control over them, so the particles of these wastes are dispersed by wind currents to the surrounding population. In this research, tailings were characterized, finding in them particles smaller than 100 micron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…To evaluate the stabilization/solidification treatment, twenty different mixes were prepared to create the monoliths under study, using mining tailings samples reported in the study by Gonzalez et al, 2023 [32]. Table 1 summarizes some properties of these samples [32], with the dam as an aggregate, modified lime mortar as a binder, and water. The binder used was a modified lime mortar named C5 lime concentrate supplied by Nanocal S.A, C.V (Mexico City, Mexico).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the stabilization/solidification treatment, twenty different mixes were prepared to create the monoliths under study, using mining tailings samples reported in the study by Gonzalez et al, 2023 [32]. Table 1 summarizes some properties of these samples [32], with the dam as an aggregate, modified lime mortar as a binder, and water. The binder used was a modified lime mortar named C5 lime concentrate supplied by Nanocal S.A, C.V (Mexico City, Mexico).…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the compressive strength of these specimens increased. As tailings have a very reduced particle size [32], there is increased contact of the binder in the specimens with high lime content (1:1), enhancing the chemical processes of C-S-H gel formation at their interface. According to the literature, this results in a strengthening of the bond between the binder and the aggregate, consequently leading to an improvement in strength results [47,48].…”
Section: Effect Of Mining Tailings Encapsulation On the Properties An...mentioning
confidence: 99%
See 3 more Smart Citations